2017
DOI: 10.17116/terarkh2017891087-94
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and arterial wall stiffness: New targets in diabetic nephropathy

Abstract: In recent years, one of the promising areas in clinical medicine is the study of impaired ments in endothelial function and arterial wall stiffness, which can be referred to as one of the important predictors of cardiovascular events in patients with chronic kidney disease, including that of diabetic etiology. There is strong evidence that endothelial function and great artery stiffness may be used as reliable clinical and instrumental indicators to evaluate the efficiency of therapeutic measures and the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Як було показано в роботах низки дослідників, артеріальна жорсткість є незалежним фактором кардіоваскулярного ризику, кількоразово підвищуючи ризик кардіоваскулярних катастроф (інсульту, розшаровуючої аневризми аорти та ін.) [6].…”
Section: вступunclassified
“…Як було показано в роботах низки дослідників, артеріальна жорсткість є незалежним фактором кардіоваскулярного ризику, кількоразово підвищуючи ризик кардіоваскулярних катастроф (інсульту, розшаровуючої аневризми аорти та ін.) [6].…”
Section: вступunclassified
“…This condition results in vasoconstriction and endothelial oxidative stress that causes significant cell death and worsening of the condition of the patient with DN. 9,10 The modulation of the oxidative stress process is performed by the p66Shc protein, which is an isoform of the SHC1 gene, located in the first chromosome. p66Shc acts on the endothelial cell by increasing the production of ROS through three different mechanisms, in the cell nucleus, in the cell membrane, and in the mitochondria, In the nucleus, p66Shc is mediated by Forkhead Box Sub-Group O (FOXO), resulting in decreased expression of the enzymes ROS-scavenging catalase (CAT) and manganese superoxide dismutase (MnSOD), both responsible for regulating ROS levels during cellular oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that functional impairment of the arterial wall can be detected well before symptoms of CVD are present [ 2 , 3 ]. There are several studies that have also shown a potential link between endothelial dysfunction and arterial stiffness specifically in hypertensive individuals, which suggest that they may be used as a critical tool to evaluate the progression of CVD [ 4 , 5 ]. The occurrence of arterial stiffness, hypertension, and related cardiovascular diseases is higher in aged populations as compared to younger counterparts [ 6 ].…”
Section: Introductionmentioning
confidence: 99%